Construction of doped-rare earth (Ce, Eu, Sm, Gd) WO3 porous nanofilm for superior electrochromic and energy storage windows. (20th April 2022) - Wang, Yongxiang; Shen, Guocan; Tang, Ting; Zeng, Jinming; Sagar, Rizwan Ur Rehman; Qi, Xiaopeng; Liang, Tongxiang
Highlights: WO3-RE (RE=Ce, Eu, Sm, Gd) nanofilms were prepared using one-step hydrothermal. WO3-RE exhibited high optical contrast, fast switching speed, and excellent stability. The optical contrast of WO3 -Sm nanofilm was greater than 68.3% in the 500–1100 nm range. The areal capacitance of the WO3 film were increased by around 351% by doping Sm ions. Abstract: Electrochromic capacitors are attracting a huge attention due to their dual functions in energy-saving and energy storage. Electrochromic and energy storage performance of the films could be effectively improved through regulating their physical phase and morphology. In the present work, the physical phase and morphology of the WO3 nanofilms were regulated by doping RE ions (RE = Ce, Eu, Sm, Gd) using one-step hydrothermal technology. The three-dimensional (3D) urchin-like crystal WO3 nanofilm would transfer into the 3D nest-like WO3 (WO3 -RE) nanofilms that consisted of crystal and amorphous phase by doping RE ions. Compared with the pure WO3 nanofilm, the WO3 -RE nanofilms exhibited higher optical contrast, faster switching speed, longer cyclic stability, and larger areal capacitance owing to faster ions transfer rate and more stable film structure. The optical contrast of WO3 -Eu and WO3 -Sm nanofilms were 76.3% and 73.8% at 633 nm, 75.5% and 74.6% at 900 nm wavelength, respectively. Notably, the WO3 -Eu and WO3 -Sm nanofilms could retain 99.6% and 99.1% of their original optical contrasts after 1000 cycles, respectively. Additionally, the areal capacitance of ECDs based on the WO3 /PB, WO3 -Ce/PB, WO3 -Eu/PB, WO3 -Sm/PB, and WO3 -Gd/PB were 26.15, 49.27, 58.23, 71.46, and 79.52 mF/cm 2 at 0.3 mA/cm 2, respectively. ECDs based on the WO3 -RE/PB are promising for energy-saving and energy storage dual functional smart windows. Abstract : Image, graphical abstract .